Verbal and Nonverbal Memory in Hemispherectomy: Lateralization Effects - Wilson, Rodney; Marion, Sarah; Asarnow, Robert; Mathern, Gary (Journal of Pediatric Epilepsy, 2017)
Hemispherectomy is a routine surgery performed for children with intractable seizures and often in the midst of a life-threatening emergency such as status epilepticus. As the following article will demonstrate, studies of neurocognitive outcome in general, and memory in specific, following hemispherectomy are mixed, although findings tend to indicate stronger lateralization of verbal memory. This is often demonstrated by loss of verbal memory following left hemispherectomy, although there are few studies focusing solely on hemispherectomy and neurocognitive outcome. We examined data from 25 patients who participated in the University of California, Los Angeles (UCLA) Pediatric Epilepsy Surgery Program (right hemisphere = 7; left hemisphere = 18). The California Verbal Learning Test-Children's Version was used as a verbal memory correlate, and the doors visual recall was used as a correlate of nonverbal memory. Based on a review of the literature, we hypothesized that (1) verbal memory would be significantly different between hemispheres with higher scores in the remaining left hemisphere; (2) nonverbal memory would be significantly different between hemispheres with higher scores in the remaining right hemisphere. Exploratory analyses were also undertaken. Implications for lateralization, medical factors, and plasticity are discussed.
Keywords: hemispherectomy; verbal memory; nonverbal memory; surgical outcome; memory; neuropsychology